Determinants of Competitiveness Among Georgian Commercial Banks in the Financial Market - Natia Gadelia (European Scientific Journal, ESJ, 2025)
This study investigates the competitiveness of Georgian commercial banks by examining their financial performance, market positioning, and the role of innovation in achieving and maintaining market leadership. A stable and efficient banking sector is fundamental to a country’s economic health, as commercial banks facilitate the allocation of financial resources and support sustainable growth. However, bank failures can pose systemic risks and undermine public trust. The research employs a mixed-method approach, combining quantitative analysis of key financial indicators with qualitative assessment through structured interviews with banking professionals. The financial data was collected from annual reports and official statistics of leading Georgian banks, while interviews provided insights into strategic management practices and innovation-driven competitiveness. The results indicate that JSC TBC Bank and JSC Bank of Georgia have maintained strong market positions through diversified financial services, customer-centric innovations, and strategic segmentation. Furthermore, banks like JSC ProCredit Bank and JSC Credo Bank have established niche competitiveness by focusing on SME lending and inclusive finance models. The findings highlight that technological adaptation, effective risk management, and customer satisfaction are critical determinants of competitiveness in the Georgian banking sector. In conclusion, the study reveals that both financial robustness and non-financial capabilities, such as innovation and managerial efficiency, contribute significantly to the sustained competitiveness of Georgian commercial banks in an increasingly dynamic and globalized financial market.